Micro-computed tomography-aided modeling for misaligned and noncircular fibers of unidirectional composites and validation under a transverse tensile loading. (18th August 2021) - Kim, Do-Won; Lim, Jae Hyuk; Kim, Sun-Won; Kim, YunHo
Abstract: An improved finite-element (FE) modeling scheme of misaligned noncircular fibers of a unidirectional composite is proposed with the aid of micro-computed tomography (μCT). The proposed scheme selects several key images among many raw CT images containing fiber misalignment and noncircular fibers. Then, it constructs two-dimensional (2D) drawings based on the signed distance obtained by solving the level-set equation with the trimmed mesh technique for phase segmentation meshing. Subsequently, these 2D drawings are bridged to construct a complex three-dimensional (3D) solid model for 3D FE model generation. To demonstrate the performance of the proposed scheme, we made an intensive comparison with other microstructure FE models in terms of the fiber volume fraction and equivalent elastic properties. Furthermore, the transverse strength was predicted through simulation and compared with the test results, showing excellent agreement with the test result that cannot be achieved with other simple modeling methods. Graphical abstract: Image 1 Highlights: A FE modeling scheme of misaligned noncircular fibers in UD composite was proposed. The complex microstructure was modeled with the aid of micro-computed tomography. . A comparative study was conducted about the transverse tensile test. The predicted transverse tensile strengths were lower than other simple predictions, showing excellent agreement with test results. This is due to the high-stress concentration that other simple models cannot simulate.